(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
This article studies the topic of the literary presentation of feminine subjectivity, both from the so-called ‘outside’ to the ‘inside’of the text and from the ‘inside’ to the ‘outside’. The former perspective is studied here in the literary creation of the character of the Monza nun, by Manzoni, who based his story on the proceedings of a real trial of a nun. The latter perspective is analyzed in the discursive creation that Sor Juana makes of herself. The analysis aims to trace the taming process that molded those subjectivities in the convent, a place where the desires and/or the thoughts of those women was subdued to the rules of a rationalized economy, whose norms where regulated and controlled by men.